Evaluasi Tata Kelola Implementasi Program Bina Keluarga Lansia (BKL) pada Masa Pandemi Covid-19 - Eva Mayasari; Ika Permanasari; Riska Epina Hayu (Jurnal Kesehatan Manarang, 2021)
One of the National Family Planning Population Board (BKKBN) programs in an effort to introduce the concept of quality families is Bina keluarga Lansia (BKL). BKL is a group of activities carried out to improve the knowledge and skills of elderly families and families who have family members aged over 60 years and over in the development, care, care, and empowerment of the elderly to improve their welfare. BKL aims to improve the quality of life of the elderly, through increasing knowledge and skills themselves entering the old age period. The purpose of this study was to evaluate the elderly family development program, the aspects evaluated in this study were input, process, and output. This research is qualitative research by conducting in-depth interviews with research informants. The results of the evaluation are known in the input section there is still a lack of human resources, funding has not been able to meet the needs, and infrastructure in the form of a special building for BKL does not yet exist. In the process of planning and implementing BKL activities, it has been going well but was hampered by the covid period. Recording and reporting have not been carried out properly, especially on the use of the online system. output is still low community participation in BKL activities. This happens because of the busyness and work of the family. The target of BKL activities is not only the elderly but also families who have the elderly, but the facts in the field are that BKL activities only focus on the elderly.